Iodine intake from supplements and diet during pregnancy and child cognitive and motor development: the INMA Mother and Child Cohort Study. Issue 3 (26th December 2017) - Murcia, Mario; Espada, Mercedes; Julvez, Jordi; Llop, Sabrina; Lopez-Espinosa, Maria-Jose; Vioque, Jesus; Basterrechea, Mikel; Riaño, Isolina; González, Llucia; Alvarez-Pedrerol, Mar; Tardón, Adonina; Ibarluzea, Jesús; et al.
Abstract : Background: The effect of mild-to-moderate maternal iodine deficiency on the neuropsychological development of their offspring is uncertain. We aimed to assess the association between iodine status during pregnancy and the cognitive and motor development of children at 4–5 years. Methods: We conducted a prospective cohort study in four Spanish regions with recruitment of pregnant women between 2003 and 2008 and follow-up of their children up to 4–5 years (mean (SD)=4.8 (0.6)). Cognitive and motor function was assessed in 1803 children using the McCarthy Scales of Children's Abilities. Dietary iodine and supplementation were measured through questionnaires twice during pregnancy. Urinary iodine concentration (UIC) was measured in spot samples. The residuals of a regression of UIC against creatinine were used to define a variable corrected for creatinine (UIC~Cr). Results: Neither iodine supplements nor iodised salt consumption or maternal UIC were associated with cognitive or motor function. After adjusting for creatinine, children of women with UIC~Cr <100 µg/L had 3.93 (95% CI −6.18 to –1.69) general cognitive scores lower than the reference (150–249 µg/L). Dietary iodine was inversely associated with motor scores and milk but not other dairy products or seafood consumption accounted for this association (beta: −1.36; 95% CI −2.12 to –0.61; per one daily milk serving). Conclusions: We found an association between low maternal urinary iodine and lower cognitive scores in childhood, although only when corrected for creatinine, adding to the evidence that iodine deficiency may have potential harmful effects on neurodevelopment. Iodine supplementation does not appear to improve child's neurodevelopment at 4–5 years.